Motivators of Prestige Brand Purchase: Testing Cultural (In)stability of Measures Over Time Across the United States, Poland, and South Korea. Issue 1 (1st January 2020) - Sung, Eunyoung (Christine); Calantone, Roger; Huddleston, Patricia
Abstract: This article encompasses two studies of how cultural dimensions help us understand consumers' motivations to buy prestige brands in the global market. In Study 1, we investigated the effects of social interaction factors on prestige brand purchase in the U.S., Poland, and South Korea. The study model was conceptualized using individualism as a cultural characteristic, drawn from Hofstede's cultural dimension theory. Consumers from these three countries represented high, medium, and low levels of individualism ( N  = 1, 816). Two data analysis procedures were conducted. After strict measurement equivalence tests, we tested our SEM and confirmed that public self-image mediates the relationship between social belonging and prestige brand purchase preference. For two countries, we found differences in social belonging effect, such that consumers with low social belonging were more likely to show high prestige brand purchase behavior. In Study 2, we tested cultural (in)stability of measures (motivators) over time using two data sets (total N  = 3, 622). Of these countries, we found that only South Korea has shifted its values over time and demonstrated intergenerational differences in prestige brand purchase preference.